(untitled) (Stato, Chiese e pluralismo confessionale, 2022)
It is lawful for the faithful to decide to no longer attend those who leave the religious community, and the announcement of the resignation to the faithful does not affect the rights of the resigning person SOMMARIO: 1. Il fatto - 2. Il punto in diritto - 3. La decisione - Sulla lesività dell’annuncio - 4. La decisione - Sull’ostracismo che sarebbe derivato dall’annuncio - 5. Conclusioni - Appendice. Abstract: A resigning member who declares that he no longer wishes to be a member of the religious organization but at the same time does not wish to cease his membership of the same confession, is not liable to compensation for psychological and economic damage following the ratification of his resignation and its communication to the local faithful. According to the court, a member’s resignation (an associative aspect) corresponds on a confessional level to no longer being considered a member of the confession. Therefore, the damaging nature of the public announcement is excluded. The general principles of law legitimize the actions of the religious organization, which also has constitutional protection in that the internal life of the religious body is regulated by its statutes, as no state interference is admissible. So-called ostracism on the part of members has no legal relevance, since it is rather the free choice of each individual to associate with someone or not, and this right is neither punishable nor harmful. The religious organization that suggests ostracizing behavior does not violate any rights as such teaching falls within the sphere of the lawful. The religious organization that suggests supposedly ostracizing behavior does not violate any legal norms, nor does it harm the interests of those who decides to cease his membership.